,если не сложно,то с решением


,если не сложно,то с решением

lasdfghjkmnbvgytfcxd lasdfghjkmnbvgytfcxd    3   15.03.2022 16:16    0

Ответы
anuta1244 anuta1244  19.03.2022 12:30

Объяснение:

на фото


,если не сложно,то с решением
ПОКАЗАТЬ ОТВЕТЫ
Оксана0990 Оксана0990  19.03.2022 12:30

Формула:    (a-b)(a+b)=a^2-b^2  .

(a-9)(a+9)=a^2-81(2+a)(2-a)=(2-a)(2+a)=4-a^2(a-16)(16+a)=(a-16)(a+16)=a^2-256(7a-2)(7a+2)=49a^2-4(a^2-5)9a^2+5)=a^4-25(5a-3b)(5a+3b)=25a^2-9b^2

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра